Religieuses et factums dans le royaume de France : exposer, dissimuler et mobiliser des soutiens (xviie et xviiie siècles) - Paul Landron (Criminocorpus)
From a sample of approximately sixty printed works, written between 1621 and 1782, we will study the use of French factums by female members of the Catholic order (collectively or individually), as well as by their adversaries to mobilize, claim or denounce support during a legal procedure. French factums in favor or against female members of the Catholic order are lacking explicit and detailed information about the networks organized to obtain justice and about the relatives involved in them. However, it is possible to associate rhetorical and judicial strategies with the practices of disclosing or concealing allies. Some allies and relatives intervening in favor of communities of female members of the Catholic order can also be revealed thanks to the French factums. This time, not through the written and printed content, but by the practical and material aspects of their elaboration and their distribution, notably towards the public prosecutor’s office.